IMPLEMENTATION OF TREND TECHNOLOGIES OF THE INDUSTRY 4.0 CONCEPT INTO THE RETAIL ACTIVITY ORGANIZATION - CHMIL, H.; POLEVYCH, K. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The research paper purpose is studying the most popular advanced technologies features of the «Industry 4.0» concept and their possibilities of dissemination, adaptation in the field of modern retail with the aim of information technology infrastructure creating for effective management of purchasing, storage (keeping) and goods’ sale processes. Research methodology. Achieving of research paper purpose is carried out with the following research methods use: logical generalization and scientific abstraction, structural analysis and analytical method. Results. The possibilities range of Big Data technology, its development prospects in retail and also organizational aspects of large data set processing are analyzed. The target orientation and RFID-technologies possibilities in the processes of supply, storage and goods sale and in the retail segment as a whole are determined. The Internet of things objects are identified, use of which will allow trade processes intensification and marketing and logistics activity optimization. «Modum.io» project is recommended; it allows controlling the goods transportation conditions, computer self-diagnostics and vehicles geolocation. Additive technologies (3D-printing) possibilities and their introduction into the retail segment are analyzed. The practical significance of the research results. The implementation into practice of the proposed digital technologies in the organizational structure of the enterprise will allow bringing the retail to new organizational, technological and economic level of development in the era of innovative and revolutionary transformations of the XXI century.